E-CRM DESIGN ON ACCESSORIES ROZI TANJUNG BALAI - Fahmi Amri; Arridha Zikra Syah; Sudarmin (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2022)
CRM is one of the means to establish a sustainable relationship between the company and its stakeholders and shareholders. So far, Rozi Accessories Store customers have to come directly to the location to be able to buy products and make transactions directly. So far, customers don't know about new products unless they have to come to the store. Customers find it difficult to check whether the product they are looking for is in the Rozi Accessories Store. By implementing Customer Relationship Management (CRM) problems that occur can be handled properly, with CRM customers no longer need to come to the location to be able to buy these products and make it easier for customers to make transactions. The results of this study are the E-CRM system produces product information to customers and facilitates transactions and can retain customers. The conclusion obtained is that E-CRM can be applied to sales of accessories to increase sales and attract new customers.